Augmenting Brief Interventions for Adolescent Marijuana Users: The Impact of Motivational Check-Ins - Walker, Denise D. (J Consult Clin Psychol, 2016)
OBJECTIVE: Brief interventions for adolescent marijuana users offered in schools reach users who otherwise would not present for treatment. The current study builds on previous trials of a school-based, two-session Motivational Enhancement Therapy (MET) intervention by adding periodic, brief motivational check-ins to reinforce gains and bolster motivation. METHODS: Adolescent participants were randomly assigned to a Motivational Check-In (MCI; n = 128) or Assessment-only Check-In (ACI; n = 124) comparison condition. Both conditions received two sessions of MET. Participants in the MCI condition then attended three MET-based check-in sessions at 4-, 7-, and 10-months after baseline, while the ACI condition participants attended assessment-only check-ins at the same time points. Optional cognitive behavior therapy (CBT) sessions were available as needed for twelve months from baseline in both conditions. RESULTS: Outcomes were assessed at 6, 9, 12, and 15 months after baseline. Participants (59% Caucasian; 68% male; Mean age = 15.84) reported using marijuana on an average of 37 of the last 60 days and 70%% met diagnostic criteria for a marijuana use disorder. Both conditions were associated with reduced use and negative consequences that were sustained throughout the 15 months of follow-up. The MCI condition resulted in greater reductions at the 6-month follow-up but differences between conditions were not found at later follow-ups, and MCI participation did not increase engagement in CBT as predicted. CONCLUSIONS: Results replicated the efficacy of the brief intervention for adolescent marijuana use and provided mixed evidence on the utility of adding repeated check-in sessions.